Interactive mathematics learning system (EMath) / Deepa Govindan - Deepa, Govindan (2000)
Interactive Mathematics Learning system is a web based multimedia learning system for lower primary school level. The target users are lower primary school students, teachers and parents. It can be used either as a teaching tool or a self learning program. This system provides lessons to educate students of 7 and 8 years of age. It can also be used by preschool children. At the end of every lesson.short test and quiz will be given to test the understanding of the students. Games based on the basic mathemahics operations are also created to test the students skills in mathematics. The aim of the system is to create an effective and interesting learning and teaching tool and environment to enable students learn mathematics and at the same time enjoy the lessons. This web based system can also promote and encourage the use of computers at an early age. This would enhance the computer literacy of students and also teachers. The development model used to develop this system is the waterfall model combined with the prototype model. The main advantage of this system is that the process can be tailored to meet the specific requirement yet possibly changing the needs of the application. The tools that will be used for this interactive multimedia system comprises of Macromedia Dreamweaver, Macromedia Flash and Microsoft Agent Scripting Helper. The programming languages that will be used are HTML, Javascript and also ASP to develop the system. The mam features of this system is that it's user friendly with an attractive interface, easy to navigate, interactive, and interesting with a talking wizard which serves as a guide and also tutor.